2019
DOI: 10.1002/cam4.2729
|View full text |Cite
|
Sign up to set email alerts
|

Jupiter microtubule‐associated homolog 1 (JPT1): A predictive and pharmacodynamic biomarker of metformin response in endometrial cancers

Abstract: Preoperative use of metformin in obese women with endometrioid endometrial cancer (EEC) reduces tumor proliferation and inhibits the mammalian target of rapamycin pathway, though is only effective in select cases. This study sought to identify a predictive and/or pharmacodynamic proteomic signature of metformin response to tailor its pharmacologic use. Matched pre-and post-metformin-treated tumor tissues from a recently completed preoperative window trial of metformin in EEC patients (ClinicalTrials.gov: NCT01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Epidemiological evidence suggested it is associated with improved survival in women diagnosed with EAC [23][24][25]. Ongoing trials will determine the effectiveness of metformin in window of opportunity studies in EAC [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological evidence suggested it is associated with improved survival in women diagnosed with EAC [23][24][25]. Ongoing trials will determine the effectiveness of metformin in window of opportunity studies in EAC [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Next, it was further figured out the downstream target genes of miR-513-5p. JPT1 is a protein-coding gene that impacts cell apoptosis and signal transduction (Bateman et al, 2020). A previous study has clarified that JPT1 is linked with the progression of PCa (Cheng et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, among the genes closely associated with PPP1R14B expression, UBE2S, JPT1, and PTTG1 were associated with abnormal expression of endometrial cancer desiccations, proliferation, migration, methylation, and prediction of response to metformin therapy. [47][48][49][50] Our study suggested that the high expression of PPP1R14B may be related to gene mutation and tumour proliferation, invasion, and metastasis in UCEC patients.…”
Section: Discussionmentioning
confidence: 99%